Immune-Enhancing Effect of an Ayurveda formulation Vidhara-Amalaki Yog - Minakshi Paneru; Nisha Ojha (International Journal of Ayurveda and Pharma Research, 2023)
Plant extracts and Ayurvedic polyherbal mixtures have been used to treat a variety of diseases since time immemorial. Studies on the therapeutic effects of these extracts in the treatment of various disorders are also extensively established. The synergistic effect of polyherbal medications in repairing and revitalizing the immune system is also highlighted in Ayurvedic classics. Argyreia speciosa Linn. (Elephant Creeper, Vidhara in Sanskrit; Family: Convolvulaceae) and Emblica officinalis Gaertn (Indian gooseberry, Amalaki in Sanskrit; Family: Phyllanthaceae) are important drugs explained in Ayurvedic literatures and Nighantus for their Rasayana and Bala-vardhaka properties (immunomodulatory actions). They also possess the restorative and rejuvenating powers as they act on the immune system and positively affect the response of the body towards disease causing pathogens. In this review a comprehensive account of the pharmacological activities along with the immunomodulatory activities of Vidhara- Amalaki yog (compound formulation of Vidhara and Amalaki) are included in view of the many recent findings of importance on this plant.